THE IMPACT OF REDDI ON INSTITUTIONS INCOME: A SOCIAL ACCOUNTING MATRIX APPROACH - Ulya, Nur Arifatul (Journal of Indonesian Economy and Business, 2011)
Indonesia is one of the three largest tropical forest countries. Indonesias forest area isÂ about 120.35 million hectares or about 60% of Indonesiaâs land area. Indonesiaâs forest isÂ not only important for the people of Indonesia both in terms of its ecologic and economicÂ role, but also important for the global environment, particularly in relation to climateÂ change. Forests could become carbon storage in large quantities, but also can be a sourceÂ of carbon emissions.Indonesias forests currently facing problems of deforestation and degradation, whichÂ contributed approximately 20% of global CO2 emissions, so that the IndonesianÂ government put a high attention on the issue of REDD (Reducing Emissions fromÂ Deforestation and Forest Degradation). REDD schemes is expected to assist Indonesia inÂ reducing deforestation and forest degradation for forest sustainability and provideÂ economic income from carbon trading.This paper aims to identify the impact of carbon trading under Reducing EmissionsÂ from Deforestation and Forest Degradation in Indonesia (REDDI) scheme on income ofinstitutions that consist of households, companies and government using the SocialÂ Accounting Matrix (SAM) approach. Accounting multiplier is used to calculate the impactÂ of REDDI scheme on institutions income in the year 2005.The results indicate that the impact of REDDI on institution income for the minimumÂ scenario is U.S. 0.68 billion whereas for the maximum scenario is U.S. . 28.86 billionREDDI give the greatest impact on householdsâ income (59.66%) than followed companiesÂ (28.17%) and government (12.17%).Keywords: carbon trading, deforestation, degradation, forest